Changing of the guards: Huge challenges ahead for the new ECB President - Guntram B. Wolff (Bruegel, 2011)
Jean-Claude Trichet deserves praise for fighting inflation and his handling of the financial crisis of 2007-2009. But his legacy is unfinished and we still have to see whether he will be the one who saved the euro. Important challenges remain for the incoming president. First, trust of citizens in the ECB has fallenmassively according to the Eurobarometer survey inmany euro area countries, including Germany and Greece. Trust needs to be regained. Second, the ECB's stance on Greece needs to be reversed both as regards financial sector participation and SMP. The SMP for Italy can be justified but can only be a temporary solution. The ECB will therefore have to further push for a fiscal lender-of-last-resort back-stop that can also exercise conditionality. Third, a rate cut should be considered at this point in time but upcoming political pressure to increase inflation needs to be resisted.
Keywords: 330; Zentralbank; Geldpolitik; Finanzmarktkrise; EU-Politik; EU-Staaten